Web-based decision support system for industrial operations management - Magalhaes, Ricardo (2010)
To maintain sustainability in today's' global economy industrial companies must have well managed systems and operations to keep up with competition. For this they can take advantage of using Web and Internet based technologies. Such can be achieved by accessing good management resources and methods through the Internet which otherwise would not be available and, at the same time, take advantageous of collaboration provided by networks of partners and users. Due to operations management complexity when a company does not have access to good algorithms it usually draws upon simple and empirical procedures whose quality of solutions provided tends to be poor. This is a situation that can be avoided if companies have easy access to good operations management algorithms or services. This can be possible because a pool of knowledge on industrial operations management, which has been developed by academia and industry over the years, can be made available, through the Internet, to a large community of users. This idea is explored towards development of a web-based system for Industrial Operation Management, based on a P2P network of operations management algorithms providers and users. Thus, the paper describes a web system for aiding the resolution of Operations Management problems through collaboration based on a network of distributed resources and users, web services and other Internet technology. The system adopts a P2P network architecture to create and enable a decentralized and global industrial operations management environment. It includes a set of functionalities accessed through the P2P network, which holds algorithms for solving different types of Operations Management problems. The algorithms are selected through a user-friendly interface, which is automatically generated for each specific problem context, including loading existing XML problem data documents, and searching and running algorithms on the peers belonging to the P2P network.